The Principle Of Joking In Tweets From The Twitter Account @kaesangp As A Review Of Pragmatics - Ananta Harvianty Putri; Fika Suci Ramadhin; Fatimah Nur Subkhi; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Rossi Galih Kesuma; Yerry Mijianti (International Journal of Educational Development, 2024)
This research is motivated by the use of social media Twitter which attracts its users with informative and popular content. Twitter has succeeded in reaching users from various groups, from officials to the general public. The features in it allow for unlimited communication. This research focuses on analyzing the principles of jokes in tweets from the Twitter account @kaesangp. The principle of joking is a method that is intended to offend feelings by being friendly or in the form of a basis for making conclusions that are true and false; an intentional violation of the maxims of politeness; and disclosure of taboo things in a speech. In accordance with the focus of the research objectives, pragmatic theory is used and is related to the principle of jokes. This research use desciptive qualitative approach. The listening method and note-taking technique were used as data collection methods. As the end of the research objective, results were obtained in the form of utterances in tweets from the Twitter account @kaesangp which contained utterances with the principle of joking. The research results were obtained from the classification and decomposition based on the type of joking speech, including satire, banter and jokes. The benefit of this research is to find out the principles of jokes contained in the tweets of related Twitter accounts.